Comparison of Long-Term Outcomes of Postmastectomy Radiotherapy between Breast Cancer Patients with and without Immediate Flap Reconstruction - Lee, Hsin-Hua; Hou, Ming-Feng; Wei, Shu-Yi; Lin, Sin-Daw; Luo, Kuei-Hau; Huang, Ming-Yii; Ou-Yang, Fu; Huang, Chih-Jen (PLOS ONE, 2016)
Purpose To compare the long-term clinical outcomes of postmastectomy radiotherapy (PMRT) between breast cancer patients with and without immediate transverse rectus abdominis myocutaneous (TRAM) flap reconstruction. Methods The study included 492 patients with stage II or III breast cancer who underwent modified radical mastectomy (MRM) and chemotherapy followed by PMRT between 1997 and 2011. Cox regression model and Kaplan-Meier curves were calculated, and the log-rank test was used to evaluate the differences between overall and disease-free survival rates in the 2 groups. Results Among 492 patients, 213 patients had immediate TRAM flap reconstruction. The mean follow-up was 7.2 years (range, 11–191 months). The 5-year and 10-year disease free survival rates were 81% and 76% for the TRAM flap group and 78% and 73% for the non-flap group. The 5-year and 10-year overall survival rates were 89% and 73% for the TRAM flap group and 83% and 74% for the non-flap group. Conclusions There exists no statistically significant difference in the rates of local recurrence, distant metastasis, disease-free and overall survival when comparing immediate TRAM flap reconstruction with no reconstruction. Our results suggest that immediate TRAM flap reconstruction does not compromise long term clinical outcomes in breast cancer patients requiring PMRT.